2016
DOI: 10.1002/2015gb005318
|View full text |Cite
|
Sign up to set email alerts
|

The annual cycle of gross primary production, net community production, and export efficiency across the North Pacific Ocean

Abstract: We measured triple oxygen isotopes and oxygen/argon dissolved gas ratios as nonincubation-based geochemical tracers of gross oxygen production (GOP) and net community production (NCP) on 16 container ship transects across the North Pacific from 2008 to 2012. We estimate rates and efficiency of biological carbon export throughout the full annual cycle across the North Pacific basin (35°N-50°N, 142°E-125°W) by constructing mixed layer budgets that account for physical and biological influences on these tracers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 93 publications
2
73
4
Order By: Relevance
“…Due to the spatial variability in O2, we were not able to determine the rate of change in Δ( O2/Ar) with time, which is needed for a nonsteady state calculation of NOP (equation ) [ Hamme et al ., ; Tortell et al ., ; Wilson et al ., ; Palevsky et al ., ]. For example, we can calculate a linear regression of Δ( O2/Ar) versus time over any 48 h period in Phase 2 (beginning 30 September 10:10 or later), with the 48 h period chosen to prevent diurnal cycling in O2 from biasing the slope [ Hamme et al ., ].…”
Section: Resultsmentioning
confidence: 97%
“…Due to the spatial variability in O2, we were not able to determine the rate of change in Δ( O2/Ar) with time, which is needed for a nonsteady state calculation of NOP (equation ) [ Hamme et al ., ; Tortell et al ., ; Wilson et al ., ; Palevsky et al ., ]. For example, we can calculate a linear regression of Δ( O2/Ar) versus time over any 48 h period in Phase 2 (beginning 30 September 10:10 or later), with the 48 h period chosen to prevent diurnal cycling in O2 from biasing the slope [ Hamme et al ., ].…”
Section: Resultsmentioning
confidence: 97%
“…For example, the assumption of steady state may be violated during vigorous blooms in the early growing season (Figure ). Previous studies also observed strong seasonality in the NCP [ Bushinsky and Emerson , ; Emerson , ; Fassbender et al ., ; Ostle et al ., ; Palevsky et al ., ]. Net heterotrophy and entrainment of newly exported production back into the mixed layer, more commonly observed in the fall and winter [ Bushinsky and Emerson , ; Emerson , ; Fassbender et al ., ; Kortzinger et al ., ; Ostle et al ., ; Palevsky et al ., ], are not captured by our current algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the spatial variability in O 2 , we are not able to determine the rate of change in ∆(O 2 /Ar) with time, which is needed for a non-steady state calculation of NOP (Hamme et al, 2012;Tortell et al, 2014;Wilson et al, 2015;Palevsky et al, 2016a). For example, we can calculate a linear regression of ∆(O 2 /Ar) versus time over any 48 h period in Phase 2 (beginning 30 September 10:10 or later), with the 48 h period chosen to prevent diurnal cycling in O 2 from biasing the slope (Hamme et al, 2012).…”
Section: Measured At 50 M Depth; All Other Methods Integrated To the mentioning
confidence: 99%